A Role for TIC55 as a Hydroxylase of Phyllobilins, the Products of Chlorophyll Breakdown during Plant Senescence. Issue 10 (21st September 2016) - Hauenstein, Mareike; Christ, Bastien; Das, Aditi; Aubry, Sylvain; Hörtensteiner, Stefan
Abstract : TIC55, a Rieske-type oxygenase previously described as a component of the chloroplast protein import machinery, also functions as a chlorophyll catabolite hydroxylase. Abstract: Chlorophyll degradation is the most obvious hallmark of leaf senescence. Phyllobilins, linear tetrapyrroles that are derived from opening of the chlorin macrocycle by the Rieske-type oxygenase PHEOPHORBIDE a OXYGENASE (PAO), are the end products of chlorophyll degradation. Phyllobilins carry defined modifications at several peripheral positions within the tetrapyrrole backbone. While most of these modifications are species-specific, hydroxylation at the C3 2 position is commonly found in all species analyzed to date. We demonstrate that this hydroxylation occurs in senescent chloroplasts of Arabidopsis thaliana. Using bell pepper ( Capsicum annuum ) chromoplasts, we establish that phyllobilin hydroxylation is catalyzed by a membrane-bound, molecular oxygen-dependent, and ferredoxin-dependent activity. As these features resemble the requirements of PAO, we considered membrane-bound Rieske-type oxygenases as potential candidates. Analysis of mutants of the two Arabidopsis Rieske-type oxygenases (besides PAO) uncovered that phyllobilin hydroxylation depends on TRANSLOCON AT THE INNER CHLOROPLAST ENVELOPE55 (TIC55). Our work demonstrates a catalytic activity for TIC55, which in the past has been considered as a redox sensor of protein import into plastids. Given the wide evolutionary distribution of both PAO and TIC55, we consider that chlorophyll degradation likely coevolved with land plants.